Angiosarcoma of the heart. Issue 4 (April 1979) - Shackell, M; Mitko, A; Williams, P L; Sutton, G C
Abstract : Two cases of angiosarcomas of the heart are described. In one the tumour, which arose from the right atrium, was demonstrated during life by angiography. In the other, diagnosed only at necropsy, the tumour arose from the right ventricle. Both cases illustrate many of the typical features of this rare tumour and the difficulties of antemortem diagnosis.